2017
DOI: 10.18203/2394-6040.ijcmph20174215
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of comprehensive knowledge of HIV/AIDS among women of the reproductive age (15-49) in Uganda

Abstract: Background: Globally, HIV is the leading cause of death among women of the reproductive age and unprotected sex is the main driver of HIV transmission. Lack of accurate and complete knowledge is one of the major causes of increase in the number of new HIV infections among women in Africa. This study was aimed at finding out factors associated with comprehensive knowledge among women in the reproductive age group of 15-49 years in Uganda. Methods: Data used was drawn from 2011 Uganda Demographic Health Survey (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
25
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 5 publications
20
25
1
Order By: Relevance
“…The study also revealed that AGYW from rich households, those who were working as well as those who were listening to radio at least once a week had high overall HIV/AIDS knowledge compared to their counterparts. These results are consistent with previous research conducted in Sub-Saharan African Countries, where most of the participants who had good knowledge about HIV/AIDS were working, listening to radio frequently and were from rich households [12,23]. A possible explanation for these ndings is that AGYW from rich households and those employed can easily afford and access information from media and other socio platforms compared to their counterparts.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The study also revealed that AGYW from rich households, those who were working as well as those who were listening to radio at least once a week had high overall HIV/AIDS knowledge compared to their counterparts. These results are consistent with previous research conducted in Sub-Saharan African Countries, where most of the participants who had good knowledge about HIV/AIDS were working, listening to radio frequently and were from rich households [12,23]. A possible explanation for these ndings is that AGYW from rich households and those employed can easily afford and access information from media and other socio platforms compared to their counterparts.…”
Section: Discussionsupporting
confidence: 91%
“…The present study also found that young women aged 20-24 years were more likely to have high overall knowledge about HIV/AIDS compared to adolescent girls aged 15-19 years. This con rms ndings of studies elsewhere [22,23]. The possible reason why adolescent girls have low overall knowledge about HIV/AIDS is limited access to health-related information.…”
Section: Discussionsupporting
confidence: 77%
“…Despite mass media plays a significant role in reducing the incidence of HIV/AIDS through raising comprehensive knowledge towards HIV/AIDS, most of the reproductive-age women in developing countries including Ethiopia have poor comprehensive knowledge of HIV/AIDS. For example, in Sub-Saharan Africa Uganda, only 38% of reproductive-age women had a comprehensive knowledge of HIV/AIDS [14]. Besides, in Ethiopia especially in Afar, Gambella, Dire Dawa, and Somali regions were detected poor knowledge of HIV/AIDS among reproductive-age women [15].…”
Section: Introductionmentioning
confidence: 99%
“…In Uganda, research found that the level of comprehensive HIV knowledge is lower (38%) among women aged 15-49. Age, wealth, place of residence, access to information and having tested for HIV were stronger determinants of comprehensive HIV knowledge [15]. Using Demographic and Health surveys for 2003-2013, research showed that comprehensive HIV knowledge increased significantly within the three period of surveys despite the lag behind the expected target among the young people in Nigeria.…”
Section: Introductionmentioning
confidence: 96%